(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
As Turkestan modernists began to prepare various programs and textbooks for new method schools, this process directly became a prelude to the creation of the country’s national history, geography, culture, and literary studies. Attempts to form the history, theory, and literary criticism of the national literature first began in the national press, and later rose to the main stage in literature textbooks written for middle and upper classes. Here is one of such textbooks - "Amaliy ham nazariy adabiyot darslari" written by Abdurahman Sa’di was published in March 1924 in Tashkent.